2022
DOI: 10.3389/fpsyg.2022.758032
|View full text |Cite
|
Sign up to set email alerts
|

Families with high-risk characteristics and diagnoses of attention-deficit/hyperactivity disorder, autism spectrum disorder, intellectual disability, and learning disability in children: A national birth cohort study

Abstract: BackgroundA national birth cohort study was used to investigate whether high-risk family factors at 1.5-year-olds can increase the risk of attention-deficit/hyperactivity disorder (ADHD) diagnosis when children reach 5.5 years. The pathway relationship of high-risk family factors, children's developmental conditions, risk of autism spectrum disorder (ASD), and diagnosis of intellectual disability (ID), learning disability (LD), and ASD was also investigated.MethodsThe 1.5-, 3- and 5.5-year-old Taiwan Birth Coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Lower scores are associated with better or more positive outcomes. For academic performance, the mean scores were 11.49 (SD: 3.04, range: [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Behavioural issues at school or 'school behaviour' had the highest score with a mean of 12.78 (SD: 4.13, range: 4-22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower scores are associated with better or more positive outcomes. For academic performance, the mean scores were 11.49 (SD: 3.04, range: [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Behavioural issues at school or 'school behaviour' had the highest score with a mean of 12.78 (SD: 4.13, range: 4-22).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that up to half of the children with ADHD have a parent with ADHD [ 2 , 13 ]. High risk familial factors directly increase the risk of ADHD diagnosis through the mediating factor of children’s development [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of both parents in a stable relationship or married is necessary for the better development of the children. The presence of parents can assist in the development of appropriate interventions to further support the children [ 28 ]. In several aspects, the presence of parents is necessary, as demonstrated by Crane et al [ 29 ] with autistic parents who found it easier to talk to their children about of patient with ASD and how to face life.…”
Section: Discussionmentioning
confidence: 99%
“…There are other cases as well where parents may also experience a sense of risk despite an apparently typical pregnancy and birth. Parents of infants who have a sibling with a diagnosed developmental impairment, such as autism spectrum disorder (ASD), fall into this category based on suggested familial risk [ 6 ]. As is the current clinical thinking relative to CP, detection of signs of ASD as early as possible [ 7 , 8 ] facilitates the introduction of interventions most likely to be effective in maximizing positive outcomes.…”
Section: Introductionmentioning
confidence: 99%